ICA SAHR – The Rwanda Gacaca Archive - Peter Horsman - ICA International Council on Archives (2022)
Peter Horsman, Professor Emeriti – University of Amsterdam presents Documenting Genocide Justice: The Rwanda Gacaca Archive Peter Horseman previously worked with the Netherlands Archives School, Municipal Archives of Dordrecht, and the National Archives of the Netherlands. Currently, he is active as a consultant, mostly in the field of (electronic) records and archives management, and digital preservation (both for public and private organizations). He is currently involved in a data transformation project, providing access to the archives of the genocide courts in Rwanda, for the Netherlands Institute for War, Holocaust and Genocide Studies (NIOD). Between 2002 and 2012, over 12,000 of Rwanda state-supervised community courts judged the alleged perpetrators of the 1994 genocide against an estimated 800,000 Tutsis by government forces, militia and Hutu civilians. The so called Gacaca Archive contains the files created before, during and after the reported 1,958,634 cases tried through these courts. Altogether, the Gacaca Archive comprises one of the world’s largest repositories on transitional justice. Gacaca refers to ‘a bed of soft green grass’ on which local Rwandan communities traditionally gathered to settle disputes between families or community members. This Gacaca juridical system, abandoned in the 1950s was reintroduced but replaced by the modernized, professionalized and centralized Inkiko Gacaca (Gacaca jurisdictions) in the early 2000s, specifically designed to deal with genocide related cases. The Gacaca Archive, about 6 linear kilometers of shelves, has been digitized, and is currently being indexed to make it accessible for both lawyers, general public, and scholars.